Representasi Sosial tentang Disabilitas Intelektual pada Kelompok Teman Sebaya - Ira Retnaningsih; Rahmat Hidayat (Jurnal Psikologi, 2012)
The purpose of this study was to examine the social representations of intellectual disability among children of 7 and 11 years old. The qualitative differences on social representations among children from villages of high- and low-prevalence of intellectual disabilities were examined. The study utilized a modified focused-group discussion with children in which participants responded to a set of vignettes depicting hypothetical situations normally confronted by children with intellectual disability. The results of analysis indicated that the peer groups hold beliefs with regards to intellectual disability as a form of mental or behavioral disorder. They showed understanding that children with intellectual disability are capable of demonstrating well-functioned intrapersonal and interpersonal skills. Nevertheless, respondents reflected their beliefs that intellectually disabled children are restricted in terms of linguistic and bodily/kinesthetic intelligence. Differences between children from the low and high prevalence areas of intellectual disability were identified, in which the latter showed more refined understanding of intellectual disability. Direct interaction and socialization from the parents are the likely sources for the observed differences. Keywords: social representations, intellectual disability, peer group